2002
DOI: 10.1089/08828240260066297
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Cell-Mediated Immunity in Pigs Infected with Porcine Parvovirus

Abstract: Porcine parvovirus (PPV) is an ubiquitous pathogen causing reproductive failure in swine. Protection against reproductive failure caused by acute PPV infection has commonly been related to the presence of specific antibodies in the dam. However, the role of cell-mediated immunity during chronic PPV infection remains to be elucidated, and may be relevant to the pathogenesis of novel diseases such as postweaning multisystemic wasting syndrome (PMWS), which may be triggered by coinfection with PPV and porcine cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…28 This hypothesis, ie PPV-specific cellular immune responses being a major differentiating factor in protective capacity, is further and specifically supported by the already demonstrated development of PPV-specific CMI evoked by PVX; briefly, in a trial where SPF pigs were vaccinated with PVX at D0, D21, and D154, antigenspecific IFNγ + T cell responses were measured upon vaccination, which was significantly boosted 4 months later, 29 similar to that of repeated PPV infection. 27 In agreement with previous findings, 18 this study also demonstrated that vaccination with commercially available inactivated vaccines cannot prevent infection since all groups responded to the challenge with antibody titer rise. However, there is a difference between the "readiness" provided by the different vaccines, which is plausibly manifested in the timely activation of memory B-cells and T-cells against infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…28 This hypothesis, ie PPV-specific cellular immune responses being a major differentiating factor in protective capacity, is further and specifically supported by the already demonstrated development of PPV-specific CMI evoked by PVX; briefly, in a trial where SPF pigs were vaccinated with PVX at D0, D21, and D154, antigenspecific IFNγ + T cell responses were measured upon vaccination, which was significantly boosted 4 months later, 29 similar to that of repeated PPV infection. 27 In agreement with previous findings, 18 this study also demonstrated that vaccination with commercially available inactivated vaccines cannot prevent infection since all groups responded to the challenge with antibody titer rise. However, there is a difference between the "readiness" provided by the different vaccines, which is plausibly manifested in the timely activation of memory B-cells and T-cells against infection.…”
Section: Discussionsupporting
confidence: 92%
“…These results are questioning the use of serological methods (ie ELISA and VN) for the evaluation of vaccine-induced protection against PPV and suggest that other mechanisms or indicators for immunity should be involved to properly evaluate the protection level of the gilts than serology. In fact, the early IFN-γ and INF-α activation in pigs upon PPV1 infection 26 and the role of the memory B cells-helper T cell complex of the cell-mediated immunity (CMI) are proven in the induction of immune response to PPV, 27 as also proven for the human adenoassociated viruses. 28 This hypothesis, ie PPV-specific cellular immune responses being a major differentiating factor in protective capacity, is further and specifically supported by the already demonstrated development of PPV-specific CMI evoked by PVX; briefly, in a trial where SPF pigs were vaccinated with PVX at D0, D21, and D154, antigenspecific IFNγ + T cell responses were measured upon vaccination, which was significantly boosted 4 months later, 29 similar to that of repeated PPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have identified a functional AP‐1 site that lies between −106 and −100 of the h2B4 promoter that strongly activates transcription. Many studies in different systems have shown that activation of transcription can involve signalling pathways that include PKC 29–31 . To examine whether PKC influenced 2B4 gene transcription through AP‐1, we mutated the (−111 to −89) sequence of the h2B4 promoter with the AP‐1 binding site from TGAGTCA to TGccgCA and synthesized mutant promoter constructs p‐M188 and p‐M342 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hardly anything is known about the role of cellular immunity in controlling PPV infection. The only investigation made in this direction found weak cytotoxic T cell (CTL) activity, suggesting that T-cell activation may occur with repeated exposure to the virus, but confirmed that effective clearance of PPV infection is obtained by rapid antibody response in infected pigs [ 55 ].…”
Section: Immunity and Preventionmentioning
confidence: 99%
“…Many immunological studies proved that the presence of neutralizing serum antibodies is a decisive factor in the outcome of the PPV infection [ 5 , 44 , 55 , 56 ]. Since the placenta is impermeable to maternal antibodies, neonatal piglets obtain passive protection against PPV1 by taking up maternally derived antibodies (MDA) from the colostrum.…”
Section: Immunity and Preventionmentioning
confidence: 99%